The efficiency of the use of the technology of the cement board of "lego-tile" - Butenko, V.; Nesterenko, І. (Ways to Improve Construction Efficiency, 2019)
Today in the construction industry there is a shortage of personnel and insufficient level of training and this is a big problem . The volume of brick construction is growing every year, the construction of stone buildings on individual projects is increasing, and it is very difficult to find a good Mason these days. In the article we consider the material and technology of brickwork, solving this problem.